2009
DOI: 10.1111/j.1365-2486.2008.01742.x
|View full text |Cite
|
Sign up to set email alerts
|

Spatio‐temporal impact of climate change on the activity and voltinism of the spruce bark beetle, Ips typographus

Abstract: The spruce bark beetle Ips typographus is one of the major insect pests of mature Norway spruce forests. In this study, a model describing the temperature-dependent thresholds for swarming activity and temperature requirement for development from egg to adult was driven by transient regional climate scenario data for Sweden, covering the period of 1961-2100 for three future climate change scenarios (SRES A2, A1B and B2). During the 20th century, the weather supported the production of one bark beetle generatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
205
4
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 253 publications
(224 citation statements)
references
References 32 publications
13
205
4
2
Order By: Relevance
“…Nonetheless, our study showed that the thermal conditions in southern Sweden during each of the study years would have allowed the development of a second generation. This is in accordance with calculations by Jönsson et al (2009), which indicated that even with the current climate; a fully developed second generation can be expected in some years each decade. With global warming, we can expect a second generation of I. typographus to occur more frequently in Fennoscandia (Lange et al, 2006;Schlyter et al, 2006;Jönsson et al, 2007Jönsson et al, , 2009.…”
Section: Voltinismsupporting
confidence: 93%
See 2 more Smart Citations
“…Nonetheless, our study showed that the thermal conditions in southern Sweden during each of the study years would have allowed the development of a second generation. This is in accordance with calculations by Jönsson et al (2009), which indicated that even with the current climate; a fully developed second generation can be expected in some years each decade. With global warming, we can expect a second generation of I. typographus to occur more frequently in Fennoscandia (Lange et al, 2006;Schlyter et al, 2006;Jönsson et al, 2007Jönsson et al, , 2009.…”
Section: Voltinismsupporting
confidence: 93%
“…This is in accordance with calculations by Jönsson et al (2009), which indicated that even with the current climate; a fully developed second generation can be expected in some years each decade. With global warming, we can expect a second generation of I. typographus to occur more frequently in Fennoscandia (Lange et al, 2006;Schlyter et al, 2006;Jönsson et al, 2007Jönsson et al, , 2009. The thermal sums that we have presented here could be used to improve parameterization of simulation models in southern Sweden, since they are both more region specific and based on a higher number of replicates of localities and years than previous data sets that had been used for simulations of bark beetle population dynamics in this region (Harding and Ravn, 1985;Jönsson et al 2007Jönsson et al , 2011.…”
Section: Voltinismsupporting
confidence: 93%
See 1 more Smart Citation
“…In short-lived species, warmer temperatures and longer growing seasons may allow additional generations per year (e.g. Tobin et al 2008;Jö nsson et al 2009;Altermatt 2010). Both of these possibilities have major implications for population growth.…”
Section: Ecological Effects Of Phenologymentioning
confidence: 99%
“…models of insect life cycle events) employ species-and life stage-specific temperature requirements towards a more process-based representation of an insect's climate dependency (Gaylord et al, 2008). Such approaches have been developed for important insect pest species, such as Ips typographus (L.) (Wermelinger and Seifert, 1998;Netherer and Pennerstorfer, 2001;Netherer and Nopp-Mayr, 2005;Baier et al, 2007: PHENIPS;Jönsson et al, 2007Jönsson et al, , 2009 and Lymantria dispar (L.) (Logan and Bentz, 1999;Gray, 2004;Powell and Logan, 2005;Pitt et al, 2007). Incorporating species-specific diapause regulation into such models was found crucial for predicting the response to driving climate variables (Gray et al, 2001;Steinbauer et al, 2004;Dolezal and Sehnal, 2007;Tobin et al, 2008).…”
Section: Occurrencementioning
confidence: 99%